The Experiences of Waste Collection Workers in Implementing an Occupational Safety and Health Culture: A Qualitative Study - Yusrianto (PT. Nasyah Medika Care, 2025)
Background: Waste collection workers face biological, physical, mechanical, ergonomic, and environmental hazards during their daily activities. However, their experiences in implementing occupational safety and health culture remain underexplored. Research Objective: This study aimed to explore the experiences of waste collection workers in implementing occupational safety and health culture. Methods: This qualitative descriptive study involved 15 waste collection workers selected through purposive sampling. Data were collected through face-to-face semi-structured interviews and non-participant observations. The data were analysed thematically through familiarisation, coding, categorisation, theme development, review, and interpretation. Trustworthiness was ensured through triangulation, member checking, peer discussion, and an audit trail. Results: Four themes were identified: daily exposure to multiple occupational hazards, inconsistent use of personal protective equipment, experience-based safety practices and peer support, and the need for stronger organisational support. Workers understood the importance of workplace safety and developed practical strategies to prevent injuries. Nevertheless, safety implementation was constrained by inadequate and uncomfortable protective equipment, limited training, hazardous working conditions, and insufficient supervision. Conclusion: Occupational safety culture among waste collection workers is shaped by individual awareness, practical experience, peer relationships, organisational commitment, and community waste-disposal practices. Adequate protective equipment, continuous training, health monitoring, supportive supervision, and community education are necessary to establish safer and more sustainable working conditions.